2017
DOI: 10.1371/journal.pone.0174487
|View full text |Cite
|
Sign up to set email alerts
|

MMP1 expression is activated by Slug and enhances multi-drug resistance (MDR) in breast cancer

Abstract: High matrix metalloproteinase 1 (MMP1) expression is associated with enhanced breast cancer growth and metastasis and also might predict poor prognosis. In this study, we further investigated the functional role of MMP1 and how it is upregulated in multi-drug resistant (MDR) breast cancer cells. By retrieving microarray data in GEO datasets and the survival data in the Kaplan Meier plotter, we observed that MMP1 is significantly upregulated in MCF-7/ADR cells compared to the parental MCF-7 cells, while high MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…promoted the growth and metastasis of esophageal squamous cell carcinoma (42). It has also been identified that MMP1 participated in breast and ovarian cancer (43,44 (46). PLOD2 has been shown to play a role in cervical cancer (35) and renal cell carcinoma (47).…”
Section: Discussionmentioning
confidence: 99%
“…promoted the growth and metastasis of esophageal squamous cell carcinoma (42). It has also been identified that MMP1 participated in breast and ovarian cancer (43,44 (46). PLOD2 has been shown to play a role in cervical cancer (35) and renal cell carcinoma (47).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, Slug can negatively regulate the transcription of multiple genes by binding to E-box motifs in their promoters, such as E-cadherin 22 and Phosphatase and tensin homolog (PTEN). 23 Recent studies found that it can activate the transcription of hexokinase-2 and MMP1 by binding to their respective promoters in breast cancer 24 , 25 and can also activate ZEB1 expression in melanoma via promoter binding. 26 In GC, increased Slug expression has well-characterized oncogenic properties and also confers malignant behaviors to the cancers.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, intercellular contacts and apical-basal polarity are lost, and tumor cell motility is enhanced via reorganization of the actin cytoskeleton and the intermediate filament network (Thiery et al, 2009;May et al, 2011). EMT-associated transcription factors can also stimulate secretion of gelatinases and matrix metalloproteinases (MMPs), leading to remodeling of the extracellular matrix (ECM) (Galindo-Hernandez et al, 2015;Shen et al, 2017). The induction of EMT in carcinomas can further increase tumor angiogenesis via enriching CSCs which possess the capacity to differentiate into endothelial cells and also upregulate the expression of the pro-angiogenic transcription factor VEGF-A (Fantozzi et al, 2014;Delgado-Bellido et al, 2017).…”
Section: Escape From the Primary Tumor Site And Intravasation Into Thmentioning
confidence: 99%